Effect of certain disinfecting solutions and surfactant on the wettability of silicone rubber impression materials (Mustansiria Dental Journal, 2018)
Back ground: All dental impressions should be disinfected before pouring to controlcross contamination but disinfection may affect impression wettability. This studyevaluated the effect of disinfection and the use of surfactant agent on thewettability of some silicone impression materials by contact angle registration ofthe gypsum slurry on flat surfaces of the impressions.Materials and methods: addition silicone regular body –automixing type- andcondensation silicone (light body)with two types of disinfecting solutions 0.2%chlorhexidine gluconate and 1% povidone iodine for two disinfecting times andone surfactant agent (soap) were used in this study. Three treatment regimes wereinvestigated: The first group of impression materials specimens was exposed tosaliva for 5 minutes (control group). Second group of specimens was exposed tosaliva then to disinfectant agents, and third group of specimens was exposed tosaliva, disinfectants and surfactant agent (experimental groups), a computerizedphotographic procedure was used to measure the wettability of the specimens.Statistical analysis was performed by using t-est at p